2008
DOI: 10.1002/cjg2.1191
|View full text |Cite
|
Sign up to set email alerts
|

The Result of Intensive Radiosonde Observation over Wuhan

Abstract: By analyzing the intensive Radiosonde data obtained at Wuhan (30.5°N, 114°E) from Jan 11 to 15, in 2006, the amplitude and phase (the Local Time corresponding to the maximum amplitude) of the diurnal tide of temperature and wind are studied, and compared with the statistical results at other sites. Great differences between them are found in amplitude, and attributed to the strong background wind in troposphere and steady weak wind in lower stratosphere. Steady diurnal variation of temperature appears above 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The LLJ is stronger at 0200 LST, shown in the v component in Fig. 13b, and appears over urban areas with weaker intensity and thinner extension, and is located higher from the ground in the boundary layer than that over rural areas, which is consistent with the observational analyses using tethersonde data (Li and Shu 2008). Liu et al (2006) found similar behavior.…”
Section: B Analyses and Verification Of Simulation Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The LLJ is stronger at 0200 LST, shown in the v component in Fig. 13b, and appears over urban areas with weaker intensity and thinner extension, and is located higher from the ground in the boundary layer than that over rural areas, which is consistent with the observational analyses using tethersonde data (Li and Shu 2008). Liu et al (2006) found similar behavior.…”
Section: B Analyses and Verification Of Simulation Resultssupporting
confidence: 84%
“…Ren et al (2007) investigated the temperature change using observations from downtown Beijing and its nearby rural stations and found that annual and seasonal urbanization-induced warming for 1961-2000 in Beijing was generally significant. Li and Shu (2008) analyzed the impacts of Beijing city on the boundary layer nocturnal low-level jet (LLJ) using tethersonde data and showed that the LLJ over urban areas appeared at higher vertical levels than that over suburban sites. Numerical simulations by Guo et al (2006) revealed that the urban region could act to create a bifurcation zone for precipitation distribution and produce more floods.…”
Section: Introductionmentioning
confidence: 99%
“…When considering the perihelion and aphelion distances, the solar irradiance changes from 1326 to 1418 W/m 2 [24]. The I s is expressed as follows [6]:…”
Section: Improving I S Modelmentioning
confidence: 99%
“…Lunar surface temperature is one of the important and fundamental parameters to interpret the thermal characteristics of the regolith from remote-sensing thermal data, which will give clues for solving thermal models and understanding the evolution of the Moon [1][2][3][4][5]. In particular, the lunar superficial layer temperature of the lunar regolith is not only regarded as a basic boundary condition for the thermal evolution models, but also represents the outermost thermal environment of the lunar surface, which changes a lot during a lunar day [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…When perihelion and aphelion distances are considered, the solar constant varies from 1418 W•m -2 to 1326 W•m -2 , and a temperature variation of ±3 K is found at subsolar point (Racca, 1995). Furthermore, when the trajectory of the Sun-Earth-Moon system is considered according to Kepler's law and the rotation and revolution of the Moon, the relationship between the effective solar irradiance and solar irradiance is too simple and inaccurate to describe as a cosine function (Li, et al, 2008).…”
Section: Effective Solar Irradiance Modelmentioning
confidence: 99%